Prevalence of parental death among young people in South Africa and risk for HIV infection. - Operario, D; Pettifor, A; Cluver, L; MacPhail, C; Rees, H (2007)
OBJECTIVES: This study estimated the prevalence and sociodemographic characteristics of young people in South Africa who have experienced parental death and examined associations between parental death and young people's HIV status and sexual behaviors. DESIGN AND METHODS: Data were from a cross-sectional nationally representative household survey of 11,904 15- to 24-year-old South Africans. Surveys included items on sexual behavior and family composition, and oral fluid samples were collected to test for HIV status. RESULTS: The prevalence of parental death was 27.3% overall: 22.4% reported a father deceased, 7.9% reported a mother deceased, and 3.0% reported both parents deceased. Parental death was disproportionately associated with black ethnicity, impoverished household living conditions, lack of an adult guardian in the home, and not completing compulsory education levels. Controlling for sociodemographic factors, parental death among female participants was significantly associated with HIV-positive status (odds ratio [OR] = 1.25, 95% confidence interval [CI]: 1.08 to 1.44), ever having had oral sex (OR = 1.23, 95% CI: 1.02 to 1.49), ever having had vaginal sex (OR = 1.38, 95% CI: 1.19 to 1.60), and having more than 1 sex partner during the past year (OR = 1.33, 95% CI: 1.07 to 1.64). Among male participants, parental death was significantly associated with ever having had vaginal sex (OR = 1.19, 95% CI: 1.04 to 1.36) and having unprotected sex at the last sexual episode (OR = 1.23, 95% CI: 1.07 to 1.42). CONCLUSIONS: More than one quarter of young South Africans have experienced parental death. Death of a parent is associated with young female South Africans' HIV status and sexual behaviors among young female and male South Africans. HIV prevention interventions are necessary to address the specific needs of young South Africans who have experienced parental death.